2022
DOI: 10.1021/acs.organomet.2c00136
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-Directed Ortho C–H Activation of Benzyl Selenide by a Selenated NHC–Half-Pincer Ruthenium(II) Complex

Abstract: In this work, we report a selenium-directed orthovinylation of benzyl selenide using a Ru(II) catalyst. This novel reaction methodology utilizes selenium as a directing group for C− H activation and tolerates a range of substitutions on both benzyl selenide and different types of vinyls. Incorporation of the directing group is significantly easy and one-pot, and it is a commonly known laboratory reagent. Through this, an effective synthetic methodology has been established for the synthesis of organoselenium w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Aniline reacts with styrene, para-methoxystyrene, and naphthylstyrene (Scheme 3, 32−34) under standard conditions and produced the desired products in 60%, 62%, and 66% yields, respectively. A nitro-substituted styrene (35) was coupled with aniline to form a 55% yield of desired product. However, the present approach was not found suitable for substituted anilines.…”
Section: ■ Substrate Scope Of the Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aniline reacts with styrene, para-methoxystyrene, and naphthylstyrene (Scheme 3, 32−34) under standard conditions and produced the desired products in 60%, 62%, and 66% yields, respectively. A nitro-substituted styrene (35) was coupled with aniline to form a 55% yield of desired product. However, the present approach was not found suitable for substituted anilines.…”
Section: ■ Substrate Scope Of the Reactionmentioning
confidence: 99%
“…Although Pd-based catalysts are widely used in a variety of catalytic reactions, some of their critical limitations are low stability and the requirement for an inert atmosphere and a moisture-free environment. , The stability issue can be addressed by selecting the appropriate ligands to maintain the catalytic efficiency of the complex. After the first report of Shaw and Noltes, , pincer ligands have received high attention in the last five decades in the design of various Pd-pincer complexes. Recently, a new approach to use the chalcogens as one of the donor sites attracted much attention; the chalcogen (a soft donor) significantly improves the complex’s stability under ambient conditions. The N-heterocyclic carbene (NHC) based chalcogenated pincer ligands show remarkable stability, require low catalyst loading, efficiently work under ambient conditions, and provide a combination of hard and soft donor sites …”
mentioning
confidence: 99%
“…[1][2][3][4][5] Their strong σ-donor properties and ease of stereo-electronic modification at nitrogen substituent and carbon backbones of the heterocyclic skeleton have been utilized in the development of complexes with interesting properties and excellent catalytic activities. [6][7][8][9][10][11] A new subclass of NHCs, called protic-NHCs (pNHCs), which bears at least one NH functional group in the N-heterocyclic ring, has become popular in recent years with contributions from Hahn, Ikariya, Kuwata, and several other groups. [12][13][14][15][16][17][18][19][20] The pNHCs have attracted significant attention over the classical NHCs due to the existence of a proton-responsive NH group, allowing H-bonding interactions, β-deprotonations, and nucleophilic additions.…”
Section: Introductionmentioning
confidence: 99%
“…8 In 2022, our research group reported an ortho vinylation of benzyl(phenyl)selane employing selenium as a directing group. 7 Functionalizing benzyl(phenyl)selane can benefit organoselenium chemistry by providing new organoseleno compounds, because these are the most significant compounds and serve as efficient skeletons in catalytic reactions and the pharmaceutical industry. 9 Moreover, these compounds have attracted more attention in synthesis, primarily due to their impressive potential use in biological sciences as anticancer, 10 anti-Alzheimer's, 11 antimicrobial, 12 antiviral, 13 anti-inflammatory, 14 antidiabetic 15 agents, etc.…”
mentioning
confidence: 99%
“…6 Among the chalcogens, selenium has great potential to act as an efficient directing group without poisoning metal catalysts. 7 In 2020, Tang et al revealed the first instance of Se-directed C−H bond borylation of arene. 8 In 2022, our research group reported an ortho vinylation of benzyl(phenyl)selane employing selenium as a directing group.…”
mentioning
confidence: 99%